Federalism and economic development in India: An assessment - Nirvikar Singh; T. N. Srinivasan (University of California, Santa Cruz Institute for International Economics (SCIIE), 2006)
This paper examines India's federal system in the context of prospects for India's future economic growth and development. After a brief review of India's recent policy reforms and economic development outcomes, and of the country's federal institutions, the analysis focuses on the major issues with respect to India's federal system in terms of their developmental consequences. We examine the impacts of tax assignments, expenditure authority and the intergovernmental transfer system on the following aspects of India's economy and economic performance: the quality of governance and government expenditure, the efficiency of the tax system, the fiscal health of different tiers of government, and the impacts on growth and on regional inequality. In each case, we discuss recent and possible policy reforms. We make comparisons with China's federal system where this is instructive for analyzing the Indian case. Finally, we provide a discussion of potential reforms of aspects of India's federal institutions.
Keywords: 330; Föderalismus; Entwicklung; Wirtschaftswachstum; Steuersystem; Wirtschaftliche Effizienz; Indien